PM2.5‐induced oxidative stress increases adhesion molecules expression in human endothelial cells through the ERK/AKT/NF‐κB‐dependent pathway. Issue 1 (15th April 2015) - Rui, Wei; Guan, Longfei; Zhang, Fang; Zhang, Wei; Ding, Wenjun
Abstract: The aim of this study was to explore the intracellular mechanisms underlying the cardiovascular toxicity of air particulate matter (PM) with an aerodynamic diameter of less than 2.5 µm (PM2.5 ) in a human umbilical vein cell line, EA.hy926. We found that PM2.5 exposure triggered reactive oxygen species (ROS) generation, resulting in a significant decrease in cell viability. Data from Western blots showed that PM2.5 induced phosphorylation of Jun N‐terminal kinase (JNK), extracellular signal regulatory kinase (ERK), p38 mitogen‐activated protein kinase (MAPK) and protein kinase B (AKT), and activation of nuclear factor kappa B (NF‐κB). We further observed a significant increase in expressions of intercellular adhesion molecule‐1 (ICAM‐1) and vascular adhesion molecule‐1 (VCAM‐1) in a time‐ and dose‐dependent manner. Moreover, the adhesion of monocytic THP‐1 cells to EA.hy926 cells was greatly enhanced in the presence of PM2.5 . However, N‐acetylcysteine (NAC), a scavenger of ROS, prevented the increase of ROS generation, attenuated the phosphorylation of the above kinases, and decreased the NF‐κB activation as well as the expression of ICAM‐1 and VCAM‐1. Furthermore, ERK inhibitor (U0126), AKT inhibitor (LY294002) and NF‐κB inhibitor (BAY11‐7082) significantly down‐regulated PM2.5 ‐induced ICAM‐1 and VCAM‐1 expression as well as adhesion of THP‐1 cells, but not JNK inhibitor (SP600125) and p38 MAPK inhibitor (SB203580), indicating that ERK/AKT/NF‐κB is involved in the signaling pathway that leads to PM2.5 ‐induced ICAM‐1 and VCAM‐1 expression. These findings suggest PM2.5 ‐induced ROS may function as signaling molecules triggering ICAM‐1 and VCAM‐1 expressions through activating the ERK/AKT/NF‐κB‐dependent pathway, and further promoting monocyte adhesion to endothelial cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We explored the underlying mechanisms of PM2.5 ‐induced endothelial dysfucntion in EA.hy926 cells. PM2.5 exposure triggered reactive oxygen species (ROS) generation, phosphorylation of Jun N‐terminal kinase (JNK), extracellular signal regulatory kinase (ERK), p38 mitogen‐activated protein kinase (p38 MAPK) and protein kinase B (AKT), activation of nuclear factor kappa B (NF‐κB), and increase in expression of intercellular adhesion molecule‐1 (ICAM‐1) and vascular adhesion molecule‐1 (VCAM‐1) as well as adhesion of THP‐1 cells. However, ERK, AKT and NF‐κB inhibitors significantly down‐regulated PM2.5 ‐induced ICAM‐1 and VCAM‐1 expression, but not JNK inhibitor and p38 MAPK inhibitor. The results suggest that PM2.5 ‐induced ROS trigger ICAM‐1 and VCAM‐1 expressions via activation of ERK/AKT/NF‐κB pathway.